Manfaat Musik pada Penanganan Demensia - Halimsetiono, Elita (Poltekkes Kemenkes Kupang, 2025)
Introduction: People with dementia can experience depression, anxiety, and agitation due to memory loss. This can also lead to loss of independence and isolation from family and friends. Music has been proven to be an effective non-pharmacological treatment option in reducing depression, anxiety, and agitation caused by dementia. This article provides an overview of the benefits of music in treating dementia. Methods: This article is a literature review with the keywords